COVID-19 epidemic investigation study of a follow-up cohort of patients with diabetic kidney disease - Wang, Qian; Zhang, Weiguang; Zheng, Ying; Lyu, Qiang; Zhang, Ruimin; Huang, Hui; Liu, Fang; Wang, Yong; Zhang, Li; Cao, Xueying; Wu, Jie; Zhou, Jianhui; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionThe impact of coronavirus disease 2019 (COVID-19) on diabetic kidney disease (DKD) patients in China is not fully understood. This study aimed to investigate infection status in a DKD cohort post-renal biopsy and analyze vaccination and infection rates, as well as symptom severity, across various renal pathologies in DKD patients.MethodsThis epidemiological survey, centered on COVID-19, employed a Chinese DKD and renal puncture follow-up cohort. A customized questionnaire enabled standardized data gathering. It collected data on clinical characteristics, vaccination and infection statuses, and diverse pathological types. The study analyzed the relationship between vaccination and infection statuses across various pathological types, evaluating characteristics and treatment outcomes in patients with infections.ResultsIn total, 437 patients with DKD from 26 Chinese provinces were followed up for a median of 44.6 ± 20 months. COVID-19 infection, vaccination, and novel coronavirus pneumonia (NCP) rates were 73.68%, 59.3%, and 6.63%, respectively. Ten patients with NCP had severe pneumonia or died of COVID-19. Renal pathology revealed that 167 (38.22%) patients had diabetic nephropathy (DN), 171 (39.13%) had non-diabetic renal disease (NDRD), and 99 had DN and NDRD (22.65%). The DN group had the lowest vaccination (54.5%), highest all-cause mortality (3.6%), and highest endpoint rates (34.10%). Compared to patients who were not vaccinated pre-infection (117 cases), vaccinated patients (198 cases) had reduced NCP (6.6% vs. 13.7%), severity (1.0% vs. 3.4%), and endpoint (9.10% vs. 31.60%) rates.ConclusionVaccination can prevent infection and diminish COVID-19 severity in patients with DKD; therefore, increasing vaccination rates is particularly important.Clinical Trial registrationClinicalTrails.gov, NCT05888909.